Water Oxidation Reaction Mediated by an Octanuclear Iron‐Oxo Cluster. Issue 45 (18th May 2018) - Deutscher, Jennifer; Corona, Teresa; Warm, Katrin; Engelmann, Xenia; Sobottka, Sebastian; Braun‐Cula, Beatrice; Sarkar, Biprajit; Ray, Kallol
Abstract : A one‐pot synthetic procedure yields the octanuclear Fe III complex [Fe8 (µ4 ‐O)4 (µ ‐ 4‐ t Bu‐pz)12 Cl4 ] (2 ). The molecular structure of2 resembles the building units of iron‐containing minerals like magnetite, ferrihydrite and maghemite. Based on mechanistic investigation we propose that in presence of Et3 N, iron(III) pyrazolates are reduced to iron(II) pyrazolates, which then activate dioxygen to form2 . Complex2 exhibits unique spectroscopic and electrochemical properties relative to those of the previously reported Fe8 clusters based on pyrazolate ligands. Furthermore, 2 can oxidize water to hydrogen peroxide, thereby mimicking the water splitting process taking place at the surface of magnetite. Compound2 therefore acts as both structural and functional models of iron‐containing minerals. Abstract : A one‐pot synthesis of an octanuclear iron‐oxo cluster [Fe8 (µ4 ‐O)4 (µ‐4‐ t Bu‐pz)12 Cl4 ] (2 ) by dioxygen activation is reported. Compound2 represents the first example of both structural and functional models of magnetite.